2009
DOI: 10.1016/j.vaccine.2009.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Protection from Staphylococcus aureus mastitis associated with poly-N-acetyl β-1,6 glucosamine specific antibody production using biofilm-embedded bacteria

Abstract: Staphylococcus aureus vaccines based on bacterins surrounded by slime, surface polysaccharides coupled to protein carriers and polysaccharides embedded in liposomes administered together with non-biofilm bacterins confer protection against mastitis. However, it remains unknown whether protective antibodies are directed to slime-associated known exopolysaccharides and could be produced in the absence of bacterin immunizations. Here, a sheep mastitis vaccination study was carried out using bacterins, crude bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 47 publications
(52 reference statements)
0
48
1
Order By: Relevance
“…Numerous approaches have been adopted in order to identify staphylococcal surface-and cell wall-associated proteins as antigenic candidates for a vaccine against S. aureus infections (34,49,51,53,(56)(57)(58)(59)(60). However, few works have been focused on the selection of antigens that could also protect against biofilm-associated bacteria (14,(24)(25)(26). This is particularly important because S. aureus biofilms play a major role in persistent infections formed on the surface of implanted medical devices and in deep tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous approaches have been adopted in order to identify staphylococcal surface-and cell wall-associated proteins as antigenic candidates for a vaccine against S. aureus infections (34,49,51,53,(56)(57)(58)(59)(60). However, few works have been focused on the selection of antigens that could also protect against biofilm-associated bacteria (14,(24)(25)(26). This is particularly important because S. aureus biofilms play a major role in persistent infections formed on the surface of implanted medical devices and in deep tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these biofilm mediators have already been proposed as vaccine antigens against S. aureus infections. Different studies have shown that administration of deacetylated PNAG conjugated with diphtheria toxin as a carrier protein induces an immunological response that protects against S. aureus infection (14,(24)(25)(26). Furthermore, a recent study by Cywes-Bentley et al showed that PNAG or a structural variant of PNAG is a conserved surface polysaccharide produced by many pathogenic bacteria, fungi, and protozoal parasites and demonstrated that passive immunization with antibodies to PNAG protects mice against both local and systemic infections caused by many of these pathogens (27).…”
mentioning
confidence: 99%
“…More recently, biofilm matrix polysaccharides were used for development of protective immune response against S. aureus mastitis in ewes (Perez et al, 2009). This approach employs cell-free surface polysaccharide in various vehicles, bacterial unbound cells or bacterial cells embedded in their biofilm matrix in various adjuvants.…”
Section: Vaccinationmentioning
confidence: 99%
“…Low oxygen concentrations like those present in the CF sputa trigger the upregulation of ica transcription (Ulrich et al, 2007) and thus may be one important signal to induce biofilm formation in vivo. Based on these results, PIA/PNAG is now being evaluated as a vaccine candidate to protect against S. aureus infection (McKenney et al, 2000;Perez et al, 2009).…”
Section: Biofilm Formation In the Cystic Fibrosis Lungmentioning
confidence: 99%